Analytic Morrey Spaces and Bloch-Type Spaces - Ofori Samuel; Jianfei Wang; Yile Zhao (Journal of Function Spaces)
This paper is devoted to characterizing the boundedness of the Riemann-Stieltjes operators from analytic Morrey spaces to Bloch-type spaces. Moreover, the boundedness of the superposition operator and weighted composition operator on analytic Morrey spaces is discussed, respectively.